Data Encryption Dispute Resolutions under Intermediary Guidelines of Information Technology Act Challenges and Future Framework - Jha, Amaresh; Jha, Anuradha (DESIDOC Journal of Library & Information Technology, 2022)
This study introduces, explores and enlists the challenges of dispute resolution pertaining to data encryption and recommends for a policy framework for systematically addressing the grievances of social media users and intermediaries. Data encryption is essential component of ensuring privacy between the sender and receiver of the message. Any law which asks for the decryption key from the intermediaries to trace the originator of the message requires a deeper understanding of the encryption architecture. It seems that there is a gap in technology and law making pertaining to data encryption which needs to be resolved using a techno-legal framework. The data used in this study stems from an online survey carried out in India by Local Circles. The findings indicate that majority of the Social Media users are in favour of strict regulations. In line with what people think, the intermediary guidelines under the Information Technology Act makes it mandatory for the intermediaries (Social Networking Sites) to comply with the rules. But, there is lack of techno-legal framework to ensure that all disputes pertaining to data encryption and social media regulation will get resolved keeping a balance.